Monetary policy, macroprudential policy and banking stability: evidence from the euro area - Angela Maddaloni; José-Luis Peydró (European Central Bank (ECB), 2013)
We analyze the impact on lending standards of short-term interest rates and macroprudential policy before the 2008 crisis, and of the provision of central bank liquidity during the crisis. Exploiting the euro area institutional setting for monetary and prudential policy and using the Bank Lending Survey, we show that in the period prior to the crisis, in an environment of low monetary policy interest rates, bank lending conditions unrelated to borrowers' risk were softened. During the same period, we also provide some suggestive evidence of excessive risktaking for mortgages loans. At the same time, we show that the impact of low monetary policy rates on the softening of standards may be reduced by more stringent prudential policies on either bank capital or loan-to-value ratios. After the start of the 2008 crisis, we find that low monetary rates helped to soften lending conditions that were tightened because of bank capital and liquidity constraints, especially for business loans. Importantly, this softening effect is stronger for banks that borrow more long-term liquidity from the Eurosystem. Therefore, the results suggest that monetary policy rates and central bank provision of long-term liquidity complement each other in working against a possible credit crunch for firms.
Keywords: E51; E52; E58; G01; G21; G28; 330; banking stability; Macroprudential policy; monetary policy